Serotonin Modulates the Central Pattern Generator for Locomotion in the Isolated Lamprey Spinal Cord - Ronald M. Harris‐Warrick; Avis H. Cohen (1985)
ABSTRACT The central pattern generator for locomotion in the spinal cord of the lamprey can be activated in vitro by the addition of D-glutamate to the bathing saline. Serotonin has no effects when bath-applied alone, but it modulates the D-glutamate-activated swimming pattern. Three major effects are observed: (1) a dose-dependent reduction in the frequency of rhythmic ventral root burst discharge; (2) enhancement of the intensity of burst discharge, due in part to the recruitment of previously inactive motoneurones; (3) prolongation of the intersegmental phase lag. Motoneurone activation appears to result from enhanced synaptic drive from the central pattern generator; no direct effects of serotonin on the motoneurones themselves (resting potential, input resistance or threshold for action potential generation) were observed. Theoretical and experimental studies suggest that the prolongation of the intersegmental phase lag results at least in part from differential effects of serotonin on segmental oscillators in different parts of the spinal cord. Isolated caudal pieces of the cord were more strongly affected by serotonin than isolated rostral pieces. We propose that serotonin may be an endogenous modulator of the central pattern generator for locomotion in the lamprey. It may have a role in the generation of a family of related undulatory movements (swimming, crawling, burrowing) by a single central pattern generator.